Black Lives Matter in Information Literacy - Pashia, Angela (Radical Teacher, 2016)
The institutional racism addressed by the Black Lives Matter movement is encoded in many of the structures of academia, including academic libraries. As a librarian who teaches information literacy, I ask students to think about which voices are represented in the scholarly literature, make explicit the implicit biases of the way scholarly materials are organized in the library and research databases, and examine the way their own biases affect their evaluations of information. In this article, I examine some of the ways racism is build into the structure of the library and describe ways I teach students to recognize inequities in the sources they rely on for college level research.